Prism adaptation combined with eye movement training for unilateral spatial neglect after stroke: Study protocol for a single-blind prospective, randomized controlled trial - Yang, Yu-xuan; Wang, Ling-ling; Du, Juan; Luo, Yao-min; Xie, Yu-lei; Zhang, Bo; Zhang, Han (Frontiers in Neurology, 2023)
Background: Unilateral spatial neglect (USN) is a complex neurological syndrome that often reduces rehabilitation outcomes, prolongs patients' hospital stays, and decreases their quality of life. However, the current therapies for USN have varying efficacy and lack standardized treatment. We will explore a new treatment option that combines prism adaptation with eye movement training for the treatment of USN after stroke. Methods: We will conduct a single-blind, prospective, randomized controlled trial to assess the efficacy of the combined intervention (prism adaptation & eye movement training) on USN in an inpatient rehabilitation setting. The study aims to recruit 72 patients with USN after an ischemic or hemorrhagic stroke. Participants will be randomly assigned to the following three treatment groups: (1) prism adaptation (PA) group (n = 24), (2) eye movement training (EMT) group (n = 24), (3) prism adaptation & eye movement group (n = 24). All groups received 10 sessions of interventions over 2 weeks, 5 times per week. Blinded assessors will conduct a baseline assessment, a post-intervention assessment, and a follow-up assessment (two weeks post-intervention). The primary outcome measure will use Behavioral Inattention Test-Conventional Subset (BIT-C) and Catherine Bergego Scale (CBS) to assess the levels of USN. Secondary outcome measurement will assess the patient's ability to perform activities of daily living using the Modified Barthel Index (MBI). Patients who completed all treatment and assessment sessions will be included in the final analysis. Discussion: This study will explore the immediate and long-term effects of 10 sessions of combined interventions (PA&EMT) on the level of USN, functional capacity. This study has the potential to identify a new, evidence-based treatment option and provide new ideas for the treatment of USN.